Managing decentralisation : a new role for labour market policy. (Local economic and employment development., 2003)
Decentralising labour market policy is a delicate and challenging subject of political debate.  Does decentralisation really enable co-ordination of policies?  At the local level, how do we make the best use of decentralised powers?  How can greater flexibility be provided in managing policies while still guaranteeing efficiency and accountability?  To enhance responsiveness to citizens’ needs, governments increasingly decentralise the way policies are designed and implemented.  In the labour market policy area, many stakeholders, from business and local government to community groups and NGOs have been receptive.  The OECD invited leading experts and experienced policy makers and practitioners to address these questions and share their experiences in dealing with such issues. This report, supported by statistical data, summarises the lessons learnt from their experiences.  It is for researchers, leading experts, business communities, economists in government circles and NGOs.